Conservative treatment for cataract: state-of-the-art - S.Yu. Petrov; I.V. Kozlova; R.P. Poleva (РМЖ "Клиническая офтальмология")
S.Yu. Petrov, I.V. Kozlova, R.P. Poleva Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Cataract is one of the leading causes of blindness worldwide and an important medical social issue in many countries. Cataract extraction and implantation of intraocular lens is the only effective treatment. However, cataract surgery is still not available for many patients for several reasons even despite the progress in phaco surgery in the last decade as well as WHO project on eye care accessibility improvement. Among these reasons are the high cost of the surgery, inaccessibility of highly specialized health care, somatic comorbidities, and psychological unwillingness. Cataract significantly reduces working capacity and the quality of life. Despite high occurrence and scientific interest, cataract pathogensis is still an enigma. Pharmacotherapy to inhibit cataractogenesis is a promising but unexplored treatment modality. This paper addresses published data for different years on the studies on this issue. The basis for pharmacotherapy is the effect on metab olic processes in the lens to prevent oxidative stress and lens opacities. Oftan® Catachrom containts adenosine, nicotinamide, and cytochrome C. Currently, this agent is a well-studied medication used when cataract surgery cannot be performed. There is a number of clinical trias on the effect of Oftan® Catachrome on visual acuity and lens using various regimens of long-term instillations. Keywords: cataract, lens, opacity, prevention, phacoemulsification, Oftan Catachrom. For citation: Petrov S.Yu., Kozlova I.V., Poleva R.P. Conservative treatment for cataract: state-of-the-art. Russian Journal of Clinical Ophthalmology. 2019;19(4):206–210.